2020
DOI: 10.1177/2167696820968691
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-Racial Life Scripts: Relations With Ethnic-Racial Identity and Psychological Health

Abstract: Life scripts dictate the culturally appropriate order, content, and timing of autobiographical events. In the current study, we examined the ethnic-racial life scripts of American emerging adults from three ethnic-racial backgrounds. One hundred ninety-five Asian, 165 Latinx, and 45 White undergraduates produced and rated seven life events they believed to be prototypical of their ethnic-racial group and self-reported desired and perceived script normality, ethnic-racial identity (ERI), and psychological healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…For example, racial/ethnic minority group members in the United States (U.S.) are less able to meet the valued cultural stand ard of attending college due to structural barriers that inhibit their college matriculation (e.g., discrimination, academic tracking; Syed et al, 2011). Variability in the content of individuals life experiences may result in intranational variation in narrative identity, as personal continuity, and the stories one tells to achieve it, might differ based on whether one is able to meet valued cultural standards (Wilkinson & Dunlop, 2022). One example of this is that individuals from marginalized groups may tell stories that highlight their connection with other marginalized people as opposed to relating with dominant cultural narratives (Syed & McLean, 2021b).…”
Section: Constituting Continuitymentioning
confidence: 99%
“…For example, racial/ethnic minority group members in the United States (U.S.) are less able to meet the valued cultural stand ard of attending college due to structural barriers that inhibit their college matriculation (e.g., discrimination, academic tracking; Syed et al, 2011). Variability in the content of individuals life experiences may result in intranational variation in narrative identity, as personal continuity, and the stories one tells to achieve it, might differ based on whether one is able to meet valued cultural standards (Wilkinson & Dunlop, 2022). One example of this is that individuals from marginalized groups may tell stories that highlight their connection with other marginalized people as opposed to relating with dominant cultural narratives (Syed & McLean, 2021b).…”
Section: Constituting Continuitymentioning
confidence: 99%
“…Without attention to power in understanding the types of scripts that get normalized, universality can be assumed, but untested. In contrast, in a recent study, participants reported the expected life events for someone of their race-ethnicity using the life script task [43]. Like the data on cultural life scripts, there was not a universal script, but rather the content of the scripts varied by race and ethnicity.…”
Section: Contexts and Scripts Are Not Value Neutralmentioning
confidence: 74%
“…For example, McLean, Boggs, et al (2020) asked participants to provide likely life events for the typical man or woman and to rate a list of normative life events for the likelihood of occurrence and importance for typical men or women. Wilkinson and Dunlop (2020) used a similar approach to examine ethnic–racial life scripts for Asian American, Latinx, and White emerging adults, documenting variations in the nature of the scripts as well as links to ethnic identity and well-being. This approach, which has been underused, can help to understand how different groups may have different cultural expectations for the life course, shedding light on what is considered “normative” and “deviant,” as well as an understanding of how certain life events considered normative can be constraining for the marginalized group (e.g., child-rearing for women; McLean, Boggs, et al, 2020).…”
Section: Master Narratives Sound Great … But How Do You Study Them?mentioning
confidence: 99%